2011
DOI: 10.1007/s11999-010-1595-y
|View full text |Cite
|
Sign up to set email alerts
|

Hip and Spine Surgery is of Questionable Value in Spina Bifida: An Evidence-based Review

Abstract: Background Although many children with spina bifida and associated scoliosis or dislocated hips undergo spine or hip surgery, the benefits are uncertain. Questions/purposes The purpose was to perform an evidence-based review on the benefits and risks of surgery for dislocated hips and scoliosis in spina bifida.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
23
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 28 publications
(39 reference statements)
0
23
0
6
Order By: Relevance
“…Wright, who performed an evidence-based review from 1950 to 2009 regarding the benefits of spine surgery, concluded that the benefits of spine surgery were uncertain with Grade I, based on inconsistent or insufficient evidence and providing no guidance. 51 At this time, simple interventions, such as chair modifications, should be investigated as possible means for shifting the trunk to improve coronal balance and sitting function before surgical intervention. 52 Hip dislocation or subluxation is a frequent condition in patients with SB, and it can affect up to 36% of children, depending on neurological level.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Wright, who performed an evidence-based review from 1950 to 2009 regarding the benefits of spine surgery, concluded that the benefits of spine surgery were uncertain with Grade I, based on inconsistent or insufficient evidence and providing no guidance. 51 At this time, simple interventions, such as chair modifications, should be investigated as possible means for shifting the trunk to improve coronal balance and sitting function before surgical intervention. 52 Hip dislocation or subluxation is a frequent condition in patients with SB, and it can affect up to 36% of children, depending on neurological level.…”
mentioning
confidence: 99%
“…However, whether surgery improves function in these patients cannot be determined from the literature. 51 Other authors have debated whether patients with MMC should even be considered for extensive surgery to reduce hip dislocation. [58][59][60] Wright concluded that the literature provided no support for the surgical treatment of children with dislocations and with lesions above L4 who have a low probability of walking in the community beyond adolescence.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Die moderne orthopädische Behandlung der Myelomeningozele (MMC) bewegt sich im Spannungsfeld zwischen Pränataldiag-nostik und Transition. Infolge der Pränataldiagnostik, die bei MMC-Diagnose zu einer hohen Zahl von Spätabbrüchen geführt hat, und der Folsäureprophylaxe, die gezielt in betroffenen Familien oder als Nahrungszusatz gegeben wird, werden immer weniger Kinder mit MMC geboren [1]. Diese werden jedoch dank der erreichten Fortschritte bei der Behandlung wie der Fetalchirurgie, durch Shunt-Anlagen, Selbstkatheterisierung und infolge der verbesserten Fürsorge älter.…”
unclassified
“…Die orthopädische Behandlung der MMC hat sich in den vergangenen 20 Jahren verändert. Die früher übliche operative Korrektur röntgenologischer Veränderungen wurde zugunsten einer funktionellen Betrachtungsweise aufgegeben [1]. Dieser Artikel beschreibt die aktuellen Konzepte der konservativen und operativen Therapiemöglichkeiten der Gelenke der unteren Extremität und der Wirbelsäule hinsichtlich der orthopädischen Grundversorgung der Patienten mit MMC.…”
unclassified